Is Gut Microbiota a Key Player in Epilepsy Onset? A Longitudinal Study in Drug-Naive Children - Ceccarani, Camilla; Viganò, Ilaria; Ottaviano, Emerenziana; Redaelli, Maria Gaia; Severgnini, Marco; Vignoli, Aglaia; Borghi, Elisa (Frontiers in Cellular and Infection Microbiology, 2021)
Microbiota alterations have been recently investigated in individuals with epilepsy and in other neurological diseases as environmental factors that play a role, by acting through the gut-brain axis, in the pathological process. Most studies focus on the contribution of bacterial communities in refractory epilepsy and suggest a beneficial role of ketogenic diet in modulating the gut microbiota and seizure occurrence. However, they do not evaluate whether epilepsy itself alters the gut microbiota in these patients or the gut microbial community could contribute as a seizure trigger. In this pilot study, we performed 16S rRNA sequencing and investigated the gut microbial community of eight children at their seizure onset and after anti-seizure was started (one year follow-up). In drug-naive subjects, we observed a microbial signature that shared several features with those reported in refractory epilepsy, such as an increased abundance in Akkermansia spp. and Proteobacteria and a decreased relative abundance in Faecalibacterium spp. We suggest that a bacterial-mediated proinflammatory milieu, as already reported for individuals with drug-resistant epilepsy, could contribute to seizure occurrence in children with new onset of epilepsy and could vary during treatment in those who are drug-responsive.